Analisis Kebijakan Penyerahan Prasarana, Sarana Dan Utilitas Di Kabupaten Sidoarjo - Supriyanto, Bambang (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2017)
The purpose of this study is to describe and analyze the implementation of policies and strategies in the delivery of infrastructure, facilities and housing utilities in Sidoarjo from a legal standpoint, as well as the development perspective. Date analysis technique used is descriptive qualitative models. The results showed that the implementation of policy implementation of policies and strategies in the delivery of infrastructure, facilities and utilities housing in Sidoarjo influenced by several aspects, including regulatory aspects are not full ownership documents owned by the developer, negligence developer obligations, lack of coordination at each institution, and also belummempunyai complete data base regarding the infrastructure, facilities and utilities. In addition to regulatory aspects of the procedure is still considered berbilit-Sukau, inconsistent and inadequate. Given the purpose and role of each - each party must be done consistently in the submission process infrastructure, facilities and utilities, both the Government of Sidoarjo regency and the developer, so that the resulting synergies that can create the infrastructure, facilities and utilities are in short supply, both quantity and quality for the benefit of society. Alternative strategies that can be done is by setting short-term goals, medium term and long term.